2012
DOI: 10.1093/jjco/hys168
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Biliary Drainage for Obstructive Jaundice Caused by Colorectal and Gastric Cancers

Abstract: Objective: To clarify the prognostic factors for patients with obstructive jaundice due to advanced colorectal and gastric cancers who had undergone percutaneous transhepatic biliary drainage. Methods: Baseline variables and clinical outcomes were evaluated for 92 consecutive patients treated with percutaneous transhepatic biliary drainage. Results: Of the 92 patients, 32 (35%) had colorectal cancer and the remaining 60 (65%) had gastric cancer. Percutaneous transhepatic biliary drainage was successfully achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
39
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 25 publications
8
39
1
1
Order By: Relevance
“…While previous studies in patients with advanced solid malignancies have demonstrated median overall survival of up to 2.9 months, 90% of patients were eligible for chemotherapy following PBD placement (12). Kasuga et al reported that multiple liver metastases and multiple prior chemotherapy administrations were both independently associated with a poorer prognosis following PBD insertion, with median survivals of 65 and 34 days in patients with successful and unsuccessful PBD insertion (9). While the degree of hepatic tumor burden was not reported in these other studies, all patients in the current study had extensive hepatic tumor burden that may not be treated at all centers.…”
Section: Discussionmentioning
confidence: 51%
“…While previous studies in patients with advanced solid malignancies have demonstrated median overall survival of up to 2.9 months, 90% of patients were eligible for chemotherapy following PBD placement (12). Kasuga et al reported that multiple liver metastases and multiple prior chemotherapy administrations were both independently associated with a poorer prognosis following PBD insertion, with median survivals of 65 and 34 days in patients with successful and unsuccessful PBD insertion (9). While the degree of hepatic tumor burden was not reported in these other studies, all patients in the current study had extensive hepatic tumor burden that may not be treated at all centers.…”
Section: Discussionmentioning
confidence: 51%
“…[22] Previous studies have described that obstructive jaundice with poor prognostic factors could not receive survival benefit from PTBD, even though they achieved an improvement of their liver dysfunction. [23] For this reason, few studies investigated the prognostic factors that predict short survival time in these patients. [11,13,19,23] By identifying poor predictive survival factors, we believe that through pre-PTBD clinical, radiological, and laboratory data analysis, we can identify the population of patients for whom PTBD will not increase well-being or survival, and in return, such invasive procedure can be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…[23] For this reason, few studies investigated the prognostic factors that predict short survival time in these patients. [11,13,19,23] By identifying poor predictive survival factors, we believe that through pre-PTBD clinical, radiological, and laboratory data analysis, we can identify the population of patients for whom PTBD will not increase well-being or survival, and in return, such invasive procedure can be avoided. In this study, we aimed to address two main issues: the survival of patients with malignant biliary obstruction post percutaneous drainage; and to describe the prognostic factors that predict short survival time after percutaneous biliary drainage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations